Working Behavior Of Government Officials In Public Services In Dutuno Village, Paleleh District, Buol Regency - Dai, Fahria A.; Nani, Yacob Noho; Tohopi, Rustam (Universitas Negeri Gorontalo, 2025)
This study explores the work behavior of government officials in delivering public services in Dutuno Village, Paleleh District, Buol Regency. Using a qualitative descriptive approach through observation, interviews, and documentation, the research focuses on three behavioral dimensions: politeness, caring, and discipline. Findings indicate that while officials often display politeness in interactions, issues such as lateness, unresponsiveness, and occasional discrimination reduce service quality. Caring is reflected in efforts to assist citizens with administrative needs, yet delays and limited initiative remain challenges. Discipline emerged as the most pressing concern, with irregular attendance affecting efficiency and public trust. The study concludes that improving service delivery requires strengthening discipline, enhancing communication and service ethics, and adopting New Public Service principles that emphasize accountability and citizen-oriented governance.